2016
DOI: 10.1182/blood-2015-11-685032
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of Pim1 kinase is a therapeutic target for adult T-cell leukemia

Abstract: Key Points Epigenetic silencing of miR-124a leads to constitutive STAT3 and activation of downstream Pim1. Pim1 kinase signaling is constitutively activated in ATL cells and represents a novel therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…In contrast, Pim‐1 and Pim‐2 were expressed in all T‐cell lines irrespective of HTLV‐1 infection. Consistent with our results, it has recently been reported that Pim‐1 is constitutively expressed in HTLV‐1–infected T‐cell lines and ATL cells . Tax contributes to the survival of HTLV‐1–infected T cells by activating factors such as NF‐κB and AP‐1 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, Pim‐1 and Pim‐2 were expressed in all T‐cell lines irrespective of HTLV‐1 infection. Consistent with our results, it has recently been reported that Pim‐1 is constitutively expressed in HTLV‐1–infected T‐cell lines and ATL cells . Tax contributes to the survival of HTLV‐1–infected T cells by activating factors such as NF‐κB and AP‐1 .…”
Section: Discussionsupporting
confidence: 92%
“…The serine/threonine Pim protein kinase is overexpressed in many hematopoietic malignancies . The Pim family is composed of three members, Pim‐1, ‐2, and ‐3.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Kataoka et al (23), 81 ATL samples were analyzed by exome sequencing and the rate of mutation for FBXW7 was found to be much lower than in our study. However, using the same patient cohort we used in this study, we recently found a similar rate of mutation for STAT3 (25.5% in Caribbean vs. 21% for Japanese samples) (23,24). Therefore, we believe the rate of mutation may be higher for FBXW7 in the Caribbean population.…”
Section: Discussionmentioning
confidence: 50%
“…F1 mice by Pim-1 inhibition. We next treated (NZB × NZW) F1 mice with a Pim-1 inhibitor, AZD1208, which had demonstrated preclinical efficacy in several cancers (19,20,27,28). Proteinuria (according to the urinary albumin-to-creatinine ratio) was remarkably delayed in AZD1208-treated animals over the 12-week observation period (Figure 2A).…”
Section: Attenuation Of Lupus-like Syndrome In (Nzb × Nzw)mentioning
confidence: 99%